👤

Rezolvaţi ecuaţiile:

2 * (x + 2) - 6x + 12 = 3 * (5 - x)

Rezolvati urmatoarele ecuatii amplificandu-le cu un multipli comun al numitorilor tuturor termenilor din ecuaţie:

a). x-1/2 - 3x-2/4 = 2
b). 2x-1/10 - x/4 = 1 - 3x+1/8
c). 2/3 - x-1/6 + 4-3x/9 = x-5/2
d). 2 * 2x-1/3 - (x - 5) = x/8 + x+7/6
e). -2/3 = 4x+1/6 + 1/4 * (x+1) - 2

Dau coroană!


Răspuns :

1.
2(x+2)-6x+12=3(5-x)
2x+4-6x+12=15-3x
-4x+16=15-3x
-4x+3x=15-16
-x=-1
x=1


2.
a)x-[tex] \frac{1}{2} [/tex]-3x-[tex] \frac{2}{4} [/tex]
-2x-1=2
-2x=2+1
-2x=3
x=-[tex] \frac{3}{2} [/tex]

b)2x-[tex] \frac{1}{10} [/tex]-[tex] \frac{x}{4} [/tex]=1-3x+[tex] \frac{1}{8} [/tex]
2x-[tex] \frac{1}{10} [/tex]-[tex] \frac{x}{4} [/tex]=[tex] \frac{9}{8} [/tex]-3x
80x-4-10x=45-120x
70x-4=45-120x
70x+120x=45+4
190x=49
x=[tex] \frac{49}{190} [/tex]

c)[tex] \frac{2}{3} [/tex]-x-[tex] \frac{1}{6} [/tex]+4-[tex] \frac{3x}{9} [/tex]=x-[tex] \frac{5}{2} [/tex]
[tex] \frac{9}{2} [/tex]-x-[tex] \frac{3x}{9} [/tex]=x-[tex] \frac{5}{2} [/tex]
27-6x-2x=6x-15
27-8x=6x-15
-8x-6x=-15-27
-14x=-42
x=3

d)[tex]2*2x- \frac{1}{3} -(x-5)= \frac{x}{8} +x+ \frac{7}{6} [/tex]
[tex]4x- \frac{1}{3} -x+5= \frac{x}{8} +x+ \frac{7}{6} [/tex]
[tex]3x+ \frac{14}{3} = \frac{x}{8} +x+ \frac{7}{6} [/tex]
[tex]72x+112=3x+24x+28 [/tex]
[tex]72x+112=27x+28[/tex]
[tex]72x-27x=28-112[/tex]
[tex]45x=-84 [/tex]